Mechanism and Efficacy of Cu2O-Treated Fabric - Zachary Benmamoun; Trent Wyhopen; You Li; William A. Ducker (MDPI AG, 2022)
Pathogenic bacteria can remain viable on fabrics for several days and therefore are a source of infection. Antimicrobial fabrics are a potential method of reducing such infections, and advances in antimicrobial fabrics can be enhanced by knowledge of how the fabric kills bacteria. Metal oxides have been considered and used as antimicrobial ingredients in self-sanitizing surfaces, including in clinical settings. In this work, we examine how the addition of cuprous oxide (Cu2O) particles to polypropylene fibers kills bacteria. First, we show that the addition of the Cu2O particles reduces the viability of common hospital pathogens, Staphylococcus aureus, Pseudomonas aeruginosa, and Streptococcus pneumoniae, by 99.9% after 30 min of contact with the treated polypropylene. Then, we demonstrate that the main killing effect is due to the drying of the bacteria onto the cuprous oxide particles. There is also a weaker effect due to free Cu+ ions that dissolve into the liquid. Other dissolved species were unimportant. Chelation of these Cu+ ions in soluble form or precipitation removes their antimicrobial activity.